2017
DOI: 10.1177/0300985817738097
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3σ Protein Expression in Canine Renal Cell Carcinomas

Abstract: 14-3-3σ is a protein expressed in many epithelial tissues associated with essential cell functions, including cell-cycle control, apoptosis, and cytoskeletal integrity. There is a paucity of knowledge of the tumorigenesis of canine renal cell carcinomas (RCCs), and the histological origin of this tumor has not been established. This study analyzed the expression of 14-3-3σ, Ki-67, cytokeratins, and vimentin in 40 canine RCCs. Aberrant expression of 14-3-3σ was demonstrated in 15 (38%) cases and was associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In response to DNA damage, this protein plays a role in preventing DNA errors during mitosis. Previous studies indicated that SFN participated in multiple kinds of tumor, including lung [17], renal [18], liver [19], and breast [20,21] cancer. Especially for lung cancer, several studies demonstrated that SFN played as a novel oncogene, stimulating the tumor initiation, and progression of lung adenocarcinoma [8,17].…”
Section: Discussionmentioning
confidence: 99%
“…In response to DNA damage, this protein plays a role in preventing DNA errors during mitosis. Previous studies indicated that SFN participated in multiple kinds of tumor, including lung [17], renal [18], liver [19], and breast [20,21] cancer. Especially for lung cancer, several studies demonstrated that SFN played as a novel oncogene, stimulating the tumor initiation, and progression of lung adenocarcinoma [8,17].…”
Section: Discussionmentioning
confidence: 99%
“…In various human carcinomas, including those of the head and neck, cervical and vulvar carcinomas, altered 14-3-3σ expression is associated with greater invasiveness, proliferation and metastasis [15,17,35]. Furthermore, in canine inflammatory mammary carcinoma, a very aggressive type of carcinoma that resembles inflammatory breast carcinoma in women, and in canine renal cell carcinomas, there is a significant neo-expression of 14-3-3σ protein and it is an independent prognostic indicator of shorter survival time [36,37]. Expression of 14-3-3σ in tumoral cells is usually cytoplasmic, however in very aggressive neoplasms nuclear translocation can occur and is associated with cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…However, acinar structures within the intravascular emboli lacked expression of 14-3-3σ. Aberrant nuclear expression of 14-3-3σ, in a subset of cases of renal cell carcinomas, was associated with a malignant phenotype and shorter survival rate [ 43 ]. Thus, we hypothesize, in view of these findings, that expression of 14-3-3σ is associated with features of malignancy, and that neoexpression of the molecule is essential in the stage of intravascular invasion.…”
Section: Discussionmentioning
confidence: 99%
“…14-3-3σ labeling was assessed using a previously published semiquantitative scoring system [ 43 ]. The scores for the percentage (1, ≤10% cells; 2, 11–50% cells; and 3, >50% cells) and staining intensity (0, negative; 1, weak; 2, moderate; and 3, intense) of positive cells were recorded and a TIS 14-3-3σ (ranging from 0 to 9) was calculated as the product of these two parameters for each of the studied cases.…”
Section: Methodsmentioning
confidence: 99%